2016
DOI: 10.18632/oncotarget.10683
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β-stimulated β-catenin up-regulation promotes angiogenesis in human lung-derived mesenchymal stromal cells through a NF-κB-dependent microRNA-433 induction

Abstract: Considerable attentions have been focused on the treatment of lung injury using mesenchymal stem cells that can replenish damaged tissues including the blood vessels. In human lung-derived mesenchymal stem cells (hL-MSC), we investigated the potential role of an IL-1β-stimulated miR-433 pathway in angiogenesis in vitro. The expressions of miR-433 and its target genes were examined in cells treated with IL-1β. The angiogenic activity of hL-MSC was studied by cell migration and tube formation assays in which miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, several other molecular pathways may be worth exploring, such as mitogen-activated protein kinase, protein kinase B, integrin, and Wnt/b-catenin (Longmate and Dipersio, 2014;Park et al, 2018). Importantly, previous works have shown that IL-1b could activate the Wnt/b-catenin pathway, resulting in more angiogenesis (Sun et al, 2016) and increased production of MMPs (Ge et al, 2009). This signaling pathway was also shown to promote cell migration in a model of burn wound through the release of Wnt4-carrying exosomes (Zhang et al, 2015a(Zhang et al, , 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…However, several other molecular pathways may be worth exploring, such as mitogen-activated protein kinase, protein kinase B, integrin, and Wnt/b-catenin (Longmate and Dipersio, 2014;Park et al, 2018). Importantly, previous works have shown that IL-1b could activate the Wnt/b-catenin pathway, resulting in more angiogenesis (Sun et al, 2016) and increased production of MMPs (Ge et al, 2009). This signaling pathway was also shown to promote cell migration in a model of burn wound through the release of Wnt4-carrying exosomes (Zhang et al, 2015a(Zhang et al, , 2015b.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that CXCR7 plays a critical role in IL-1β-induced EPC angiogenesis, which is consistent with the findings of Watanabe, K. and colleagues in HUVECs. 40 NF-κB is a classical IL-1β-induced downstream signalling molecule that plays critical roles in IL-1β-induced angiogenesis in mesenchymal stromal cells 41 and angiogenic factor expression in temporomandibular disc cells. 34 Moreover, NF-κB and G protein-coupled receptors are closely connected in inflammation and tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…We then investigated whether the accumulation of IL1 is correlated with activation of Wnt signaling pathways. Several studies suggest that IL1 could enhance Wnt signal via inhibiting DKK1 or indirectly interacting with intracellular NF-kB and CREB signaling [12,13,22]. Based on these findings, we treated T24 cells with recombinant IL1 , and showed remarkably up-regulated expression of Wnt targets.…”
Section: Discussionmentioning
confidence: 81%